Caring Across Borders: Family Resilience among Indonesian Migrant Worker Families in the Gembok Katresnan Program - Kayyis Fithri Ajhuri; Hafidh Aziz; Elfi Muawanah (DAWUH : Islamic Communication Journal, 2026)
International labour migration may improve household economies while simultaneously intensifying emotional distance, role reconfiguration, and marital vulnerability within migrant worker families. Although studies on transnational families have documented these pressures, less attention has been paid to how village-based initiatives mediate family resilience in migrant-sending communities. This article examines the Gembok Katresnan Program in Bringinan Village, Ponorogo, Indonesia, as a community-based initiative that supports family resilience among Indonesian migrant worker families. The study employs a qualitative case study design drawing on in-depth interviews, observation, and document analysis. Guided by the Family Resilience Framework and informed by perspectives on transnational care and community support, the study explores how commitment, communication, caregiving, and social support are negotiated across borders. The findings suggest that the program operates through three interrelated processes: the public reinforcement of marital commitment, the continuity of care and communication across distance, and village-based support across the migration cycle. Read through an Islamic psychology lens, resilience is further illuminated through meanings of amanah, sabr, ikhtiar, and relational responsibility. The article argues that family resilience in transnational migrant households is not produced solely within the private sphere of the family but is co-constructed through locally embedded support systems that organize care across borders.